'First and foremost a human being…': user perspectives on mental health services from 50 mentally disordered offenders. (17th November 2018) - Møllerhøj, Jette; Os Stølan, Liv
Abstract: Background: This is the first study of this kind in a Danish context. Knowledge and research on user perspectives is rather limited in Danish as well as Nordic psychiatry. Aims: The aim of the study was to create new knowledge on patient and user perspectives and how mentally disordered offenders perceive their hopes and expectancies as well as their interactions with staff in mental health services. Furthermore, the aim was to establish what constitutes helpful care and treatment seen from a user perspective, and how the users themselves look at and perceive their sentences and how, according to them, the overall aim to prevent future crime can be fulfilled. Method: The study is based on 50 semi-structured qualitative research interviews. Main themes and patterns were condensed and synthesized in a qualitative analysis. Results: The study has provided useful knowledge of service users' experiences with nursing, treatment and rehabilitation practices. As part of the interviews, patients were asked to contribute with advice on how to improve practices within mental health services. There are remarkable similarities between the answers, and central points were reiterated from interview to interview: The importance of mental health staff acting with respect and empathy in their interaction with patients, improved communication between patients and professionals involved in clinical pathways, responsiveness and shared decision-making when adjusting medical treatment as well as a greater variety of activities offered within inpatient units. Conclusion: When asked what it is like to be a forensic patient, the informants underline that despite severe mental illness, social marginalization as well as various criminal records they are still, first and foremost, human beings. However, they often feel dehumanized and monstrous.